Novel Hyperthermophilic Crenarchaeon Thermofilum adornatum sp. nov. Uses GH1, GH3, and Two Novel Glycosidases for Cellulose Hydrolysis - Zayulina, Kseniya S.; Kochetkova, Tatiana V.; Piunova, Ulyana E.; Ziganshin, Rustam H.; Podosokorskaya, Olga A.; Kublanov, Ilya V. (Frontiers in Microbiology, 2020)
A novel hyperthermophilic, anaerobic filamentous archaeon, Thermofilum adornatum strain 1910b T , is capable of growing with cellulose as its sole carbon and energy source. This strain was isolated from a terrestrial hot spring in Kamchatka, Russia. The isolate 1910bT grew optimally at a temperature of 80°C and a pH of 5.5-6.0, producing cell-bound inducible cellulases. During genome analysis, genes, encoding various glycosidases (GHs) involved in oligo-and polysaccharide hydrolysis and genes for the fermentation of sugars were identified. No homologs of currently known cellulase families were found among the GHs encoded by the 1910b T genome, suggesting that novel proteins are involved. To figure this out, a proteomic analysis of cells grown on cellulose or pyruvate (as a control) was performed. Both in-depth genomic and proteomic analyses revealed four proteins (Cel25, Cel30, Cel40 and Cel45) that were the most likely to be involved in the cellulose hydrolysis in this archaeon. Two of these proteins (Cel30 and Cel45) were hypothetical according to genome analysis, while the other two (Cel25 and Cel40) have GH3 and GH1 domains, respectively. The respective genes were heterologously expressed in E. coli BL21 (DE3), and enzymatic activities of recombinant proteins were measured with carboxymethyl cellulose (CMC), Avicel and cellobiose as substrates. It was revealed that the Cel30 and Cel25 proteins were likely exoglucanases with side beta-glucosidase and endoglucanase activities, that Cel40 was a multifunctional glucanase capable of hydrolyzing beta-1,4-glucosides of various lengths, and that Cel45 was an endoglucanase with side exoglucanase activity. Taking into account that the cellulolytic activity of T. adornatum 1910b T surface protein fractions was inducible, that recombinant Cel25 and Cel30 were much less active than Cel40 and Cel45, and that their gene expressions were (almost) non-induced by CMC, we suggest that Cel40 and Cel45 play a major role in the degradation of cellulose, while Cel25 and Cel30 act only as accessory enzymes.2